Disentangling the effect of private and public cash flows on firm value - Cristina Mabel Scherrer; Marcelo Fernandes (Queen Mary University of London, School of Economics and Finance, 2016)
This paper presents a simple model for dual-class stock shares, in which common shareholders receive both public and private cash flows (i.e. dividends and any private benefit of holding voting rights) and preferred shareholders only receive public cash flows (i.e. dividends). The dual-class premium is driven not only by the firm's ability to generate cash flows, but also by voting rights. We isolate these two effects in order to identify the role of voting rights on equity-holders' wealth. In particular, we employ a cointegrated VAR model to retrieve the impact of the voting rights value on cash flow rights. We find a negative relation between the value of the voting right and the preferred shareholders' wealth for Brazilian cross-listed firms. In addition, we examine the connection between the voting right value and market and firm specific risks.
Keywords: G32; G34; G38; G15; 330; Private benefits; Voting right; Dual-class shares